Degradation of polycyclic aromatic hydrocarbons by the copper(II)-hydrogen peroxide system - Gabriel, J; Shah, V; Nesmĕrák, K; Baldrian, P; Nerud, F (Folia microbiologica, 2000)
A non-enzymic system containing CuSO4 (10 mmol/L) and hydrogen peroxide (100 mmol/L) was used for the degradation of three polycyclic aromatic hydrocarbons: phenanthrene, fluoranthene, and pyrene (all at 10 mmol/L). The system degraded the compounds rapidly and efficiently. After 1 d at room temperature, more than 80% of pyrene, phenanthrene, and fluoranthene disappeared. Several products are formed during the reaction including a black precipitate.
Keywords: Biodegradation, Environmental; Copper; Pyrenes; látky znečišťující životní prostředí; pyreny; peroxid vodíku; fluoreny; Hydrogen Peroxide; polycyklické aromatické uhlovodíky; biodegradace; Fluorenes; oxidace-redukce; Phenanthrenes; Free Radicals; Environmental Pollutants; měď; Oxidation-Reduction; volné radikály; Polycyclic Aromatic Hydrocarbons; fenantreny